A report into patterns of diet and exercise in the Pakistani community of Nottingham City - Shaw, Ian; Hussain, Basharat (Nottingham City Primary Care NHS Trust, 2013)
This qualitative investigation considers dietary and exercise patterns of the Pakistani community residing in Nottingham. This is an important area of inquiry as the evidence suggests that these patterns cause higher rates of CHD among the members of community. This section reports the key findings and the ways of influencing the dietary and exercise patterns of the community. Key Findings